Considering The Work of Martin Nakata's “Cultural Interface”: a Reflection on Theory and Practice by a Non-Indigenous Academic - McGloin, Colleen (The Australian Journal of Indigenous Education, 2009)
Abstract This is a reflective paper that explores Martin Nakata's work as a basis for understanding the possibilities and restrictions of non-Indigenous academics working in Indigenous studies. The paper engages with Nakata's work at the level of praxis. It contends that Nakata's work provides non-Indigenous teachers of Indigenous studies a framework for understanding their role, their potential, and limitations within the power relations that comprise the “cultural interface”. The paper also engages with Nakata's approach to Indigenous research through his “Indigenous standpoint theory”. This work emerges from the experiential and conceptual, and from a commitment to teaching and learning in Indigenous studies. It is a reflection of how non-Indigenous academics working in Indigenous studies can contribute to the development and application of the discipline.